INFLUENCE OF STRESS ON BLOOD PRESSURE, HEART RATE, LEVELS OF SALIVARY AMYLASE AND SKIN TEMPERATURE - Indah Kartika Sari, Sylvie (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2016)
Productivity is the key to improved standard of living of a Country. Productivity growth represents the key to economic success. In this perspective we could increase productivity, one through human resources productivity that represents a potential contained within each human being. From understanding of human resources, then human health is one factor that important to support good human resources. And stress is one of human health problems that can be classified as dangerous phenomenon that leads to deterioration of people’s total functioning The physiological stressors activate two stress response systems; the HPA axis (hypothalamic-pituitary-adrenal) and SAM sympatho-adrenal-medullary axis. SAM activates two regulatory systems, i.e. systems hormones norepinephrine and direct system sympathetic innervations. Both affect increased secretion of salivary amylase. Increased levels of norepinephrine associated with the increased of blood pressure, heart rate, and skin temperature. In this research we use blood pressure, heart rate, skin temperature and salivary amylase because the four physiological factors can be measured by non-invasive way and without requiring special skills. Ten people volunteered to participate in this study. All study participants were healthy adults and aged between 23 until 35 years old. All of them are not smoker. The subject consisted by five males and five females. All of them will measured their blood pressure (BP), heart rate (HR), salivary amylase, and skin temperature. Further, the experiment data will analyzed using statistical analysis – Ordinal Logistic Regression to know the influence of stress on physiological factors. Two physiological factors namely amylase and heart rate that affected by stress. For blood pressure and skin temperature revealed no effect. No effect in this case based solely on the statement of the hypothesis only. Indeed for the results of the effect of stress on blood pressure and skin temperature result still not clear. Due to it can be both factors at the time of acute stress response. While this study only used to determine the effect of stress on physiological factors immediately.